SPK Penerima Bantuan Rumah Tidak Layak Huni (RTLH) Menggunakan Simple Additive Weighting (SAW) di Desa Nglungger - Adhika Pramita Widyassari (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2022)
Housing assistance unfit for habitation is one of the government programs to overcome the poverty rate in Indonesia, however, the problem is that the process carried out by the Kelurahan is still carried out subjectively by only considering the survey results. Therefore, the kelurahan requires a decision support system so that the selection can be carried out systemically efficiently. The Multiple Attribute Decision Making method provides answers to all these problems. From several Multiple Attribute Decission Making methods, Simple Addictive Weighting is chosen to be applied to the decision support system. Purpose This decision support system is made so that the kelurahan can distribute assistance to those entitled to receive it, so that with a web-based decision support system to select recipients of uninhabitable housing assistance is appropriate and objective. This study provides fairly accurate results where the distribution process is right on target with data obtained from the kelurahan. The system created is enough to help the urban village with the results of functional tests using black box tables to get 100% results and a low error value, namely MSE of 0.000406667.